An approach to the study of G-protein-coupled receptor kinases: an in vitro-purified membrane assay reveals differential receptor specificity and regulation by G beta gamma subunits. - Pei, G (1994)
Phosphorylation of GTP-binding-regulatory (G)-protein-coupled receptors by specific G-protein-coupled receptor kinases (GRKs) is a major mechanism responsible for agonist-mediated desensitization of signal transduction processes. However, to date, studies of the specificity of these enzymes have been hampered by the difficulty of preparing the purified and reconstituted receptor preparations required as substrates. Here we describe an approach that obviates this problem by utilizing highly purified membrane preparations from Sf9 and 293 cells overexpressing G-protein-coupled receptors. We use this technique to demonstrate specificity of several GRKs with respect to both receptor substrates and the enhancing effects of G-protein beta gamma subunits on phosphorylation. Enriched membrane preparations of the beta 2- and alpha 2-C2-adrenergic receptors (ARs, where alpha 2-C2-AR refers to the AR whose gene is located on human chromosome 2) prepared by sucrose density gradient centrifugation from Sf9 or 293 cells contain the receptor at 100-300 pmol/mg of protein and serve as efficient substrates for agonist-dependent phosphorylation by beta-AR kinase 1 (GRK2), beta-AR kinase 2 (GRK3), or GRK5. Stoichiometries of agonist-mediated phosphorylation of the receptors by GRK2 (beta-AR kinase 1), in the absence and presence of G beta gamma, are 1 and 3 mol/mol, respectively. The rate of phosphorylation of the membrane receptors is 3 times faster than that of purified and reconstituted receptors. While phosphorylation of the beta 2-AR by GRK2, -3, and -5 is similar, the activity of GRK2 and -3 is enhanced by G beta gamma whereas that of GRK5 is not. In contrast, whereas GRK2 and -3 efficiently phosphorylate alpha 2-C2-AR, GRK5 is quite weak. The availability of a simple direct phosphorylation assay applicable to any cloned G-protein-coupled receptor should greatly facilitate elucidation of the mechanisms of regulation of these receptors by the expanding family of GRKs.